Cancer anorexia: hypothalamic activity and its association with inflammation and appetite‐regulating peptides in lung cancer. Issue 1 (5th October 2016) - Molfino, Alessio; Iannace, Alessandro; Colaiacomo, Maria Chiara; Farcomeni, Alessio; Emiliani, Alessandra; Gualdi, Gianfranco; Laviano, Alessandro; Rossi Fanelli, Filippo
Abstract: Background: Energy homeostasis is mediated by the hypothalamus, whose inflammation‐induced functional derangements contribute to the onset of anorexia in cancer. By using functional magnetic resonance imaging (fMRI), we determined the patterns of hypothalamic activation after oral intake in anorexic (A), non‐anorexic (NA) cancer patients, and in controls (C). Methods: Lung cancer patients were considered. Hypothalamic activation was recorded in A and NA patients and in C by fMRI, before (T0), immediately after (T1) the administration of an oral nutritional supplement, and after 15 min (T2). The grey of the hypothalamus and Blood Oxygen Level Dependent (BOLD) intensity were calculated and normalized for basal conditions. Interleukin (IL)‐1, IL‐6, tumour necrosis factor (TNF)‐α, ghrelin, and leptin plasma levels were measured. A statistical parametric mapping was used. Results: Thirteen lung cancer patients (7 M, 6 F; 9A, 4NA) and 2 C (1 M, 1 F) were enrolled. Controls had the lowest BOLD intensity. At all‐time points, anorexic patients showed lower hypothalamic activity compared with NA ( P < 0.001) (T0: 585.57 ± 55.69 vs. 667.92 ± 33.18, respectively; T1: 536.50 ± 61.70 vs. 624.49 ± 55.51, respectively; T2: 556.44 ± 58.51 vs. 615.43 ± 71.50, respectively). Anorexic patients showed greater BOLD signal reduction during T0–T1 than NA (−8.5% vs. −6.80%, P < 0.001). Independently from the presence of anorexia, BOLD signals modification before and after oral challenge correlated with basal values of IL‐1 and ghrelin ( P < 0.001). Conclusions: Hypothalamic activity in A cancer patients is reduced respect to NA and responds differently to oral challenges. This suggests a central control of appetite dysregulation during cancer anorexia, before, and after oral intake.